Penerapan Komunikasi Non Verbal Dalam Permainan Tradisional Anak - Fitrianola Rezkiki; Imelda Rahmayunia Kartika; Rina Mariyana; Hauzan Jiyad Adli (Universitas Muhammadiyah Palembang, 2025)
Traditional games are a form of play therapy for children to increase motor skills. The application of non-verbal communication when playing can make children comfortable and stimulate children to understand the concept of the game more quickly. The aim of this community service is to see the application of educators' non-verbal communication in children's traditional games, especially in seeing children's growth and development. The methods used in this PKM include; sharing information about the application of non-verbal communication in the traditional game